Empowerment Of Msmes In Hakatutobu Village Through Artificial Intelligence-Based Digital Marketing Training - Khartha, Aqzhariady; Alfian, Heri; A. Bohang, Muthmainnah Bahri; Dakka, Litha Nesidekawati; Wirawati, Nur; Nasir, Syarif Hidayat; Marhamah, Marhamah; Putra, Eko (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
This community service aimed to empower seafood processing Micro, Small, and Medium Enterprises (MSMEs) in Hakatutobu Village through digital marketing training and the utilization of Artificial Intelligence (AI). The lack of digital marketing skills and technological limitations were the main obstacles faced by partners in expanding market reach. The method employed was Participatory Action Research (PAR) combined with hands-on training for 25 participants. The core material focused on AI prompting literacy to generate effective copywriting and promotional designs. Success was measured by comparing pre-test and post-test scores and paired sample t-test. Quantitative results showed an average increase in participants' understanding of 55% (from 50.0 to 77.5), which was proven statistically significant (p < 0.001). Qualitatively, participants were able to produce their first digital promotional content. The evaluation instrument comprised 20 items assessing five digital marketing competency indicators, with face validity confirmed by expert review. The PAR approach engaged partners iteratively through planning–action–reflection cycles rather than one-way training. These findings indicate that the AI-based hands-on intervention produced a statistically significant and practically meaningful improvement in MSMEs’ digital marketing competence, enabling local processed seafood products to reach a broader market.